2017
DOI: 10.1017/s0022029917000577
|View full text |Cite
|
Sign up to set email alerts
|

Using milk leukocyte differentials for diagnosis of subclinical bovine mastitis – CORRIGENDUM

Abstract: The authors would like to apologise for a mistake in the above-mentioned article by Gonçalves et al. Checking the data, it was found that the position of false-positive and false-negative results were accidently reversed when calculating sensitivity and specificity.The following errors have been noted:On the first page, in the abstract:'When MC was considered the gold standard for mastitis diagnosis, the calculated diagnostic Se of the MLD was 65·4% (IC 95% = 57·4 to 72·8%) and the Sp was 79·3% (IC 95% = 71·4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 1 publication
4
4
0
1
Order By: Relevance
“…In more recent reports, NEU proportions ranged between 6 and 50%, LYM proportions between 14 and 80%, and MAC proportions between 12 and 46% ( Rivas et al, 2001 ; Merle et al, 2007 ; Koess and Hamann, 2008 ; Schwarz et al, 2011b ). Interestingly, our observed distribution of white cells in milk from healthy quarters was similar to that recently described by Gonçalves et al (2017) . The main cell type for healthy quarters in our study was NEU (51.4%), followed by MAC (30.1%) and LYM (17.4%).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In more recent reports, NEU proportions ranged between 6 and 50%, LYM proportions between 14 and 80%, and MAC proportions between 12 and 46% ( Rivas et al, 2001 ; Merle et al, 2007 ; Koess and Hamann, 2008 ; Schwarz et al, 2011b ). Interestingly, our observed distribution of white cells in milk from healthy quarters was similar to that recently described by Gonçalves et al (2017) . The main cell type for healthy quarters in our study was NEU (51.4%), followed by MAC (30.1%) and LYM (17.4%).…”
Section: Discussionsupporting
confidence: 90%
“…The main cell type for healthy quarters in our study was NEU (51.4%), followed by MAC (30.1%) and LYM (17.4%). In agreement, Gonçalves et al (2017) reported NEU, MAC, and LYM percentages in milk of culture negative udder quarters of 49.4, 28.9, and 17.7%, respectively.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations